Design of Training Model to Improving the Role and Function of Malin in Minangkabau Community - Adi Yalmon (Indonesian Center for Religion and Society Studies (InTReSt), 2021)
The low capacity of Malin in carrying out his duties and functions is one of the obstacles in realizing the development of nagari in West Sumatra. The purpose of this research are to (1) describe and analyze the factual model of Malin's training in the nagari community, (2) design and develop the Malin training conceptual model, (3) determine the validity of the Malin training conceptual model, (4) test the effectiveness of Malin's training hypothetical model, and (5) describe the supporting and inhibiting factors in the Malin training implementation in the Rambatan Subdistrict, Tanah Datar District, West Sumatra Province. Research and Development (R&D) research method by following the steps of ADDIE (Analyze, Design, Development, Implementation, Evaluate) model was adopted. Data collection techniques using interviews, documentation studies, observations and questionnaires. Data were analyzed using qualitative techniques by describing empirical data from preliminary studies. Trial activities in addition to testing the implementation of the model and the device are also to determine the feasibility of the model used, so as to produce the expected product. The model evaluation results are used to show, benefit, practicality and feasibility of the model developed so that the final training model is obtained. The results showed that the development of training models for Malin basically included: needs analysis and designing training models, the development of conceptual models of training began: planning, implementing, evaluating and reflecting the results of research. The implementation of the Malin problem-based training model shows that (good category) means that it is feasible and can improve Malin's knowledge and skills as a strong influence from the implementation of the developed training model. Based on the results of the significance test analysis, it can be concluded that Malin's problem-based training model has proven effective in increasing Malin's knowledge and skills in carrying out his duties and functions in the Nagari community.